Analysis of the Relationship between Spawning Stock Biomass and Demersal Fish Recruitment Using a Non-Linear Model in the Lombok Strait Waters - Andi Prayitno; Siska Amalia; Jhony Michael (Journal of Marine Fisheries, 2026)
This study analyzes the relationship between spawning stock biomass (SSB) and demersal fish recruitment in the Lombok Strait using a non-linear modeling approach. The background of this research is the importance of understanding stock-recruitment dynamics for sustainable fisheries management, particularly in heavily exploited marine areas. The objective is to identify the mathematical form of the relationship between SSB and recruitment and to evaluate the performance of Ricker, Beverton-Holt, and alternative non-linear models. The methods include time-series analysis, non-linear parameter estimation using least squares, and model evaluation based on the Akaike Information Criterion (AIC) and coefficient of determination (R²). The data consist of spawning stock biomass estimates and recruitment indices derived from fisheries catch data and surveys. The results indicate that the non-linear model provides the best fit compared to classical models, showing a clear density-dependent pattern. Increases in SSB do not always lead to higher recruitment due to environmental variability and fishing pressure. In conclusion, the SSB–recruitment relationship for demersal fish in the Lombok Strait is non-linear and strongly influenced by environmental conditions. These findings support ecosystem-based fisheries management policies.